High-spin surface FeIV = O synthesis with molecular oxygen and pyrite for selective methane oxidation - Ling, Cancan; Li, Meiqi; Li, Hao; Liu, Xiufan; Guo, Furong; Liu, Yi; Zhang, Rui; Zhao, Jincai; Zhang, Lizhi (Nature communications, 2025)
Nature-inspired high-spin Fe IV = O generation enables efficient ambient methane oxidation. By engineering sulfur-bridged dual ≡Fe II …Fe II ≡ sites on pyrite (FeS 2 ) mimicking soluble methane monooxygenase, we achieve O 2 -driven formation of high-spin (S = 2) surface Fe IV = O species at room temperature and pressure. Strategic removal of bridging S atoms creates active sites that facilitate O 2 activation via transient ≡Fe-O-O-Fe≡ intermediates, promoting homolytic O − O bond cleavage. The resulting Fe IV = O exhibits an asymmetrically distorted coordination environment that reduces the crystal field splitting and favors the occupation of higher energy d-orbitals with unpaired electrons. Impressively, this configuration can efficiently convert CH 4 to CH 3 OH through an oxygen transfer reaction with a synthetic efficiency of TOF = 27.4 h −1 and selectivity of 87.0%, outperforming most ambient O 2 -driven benchmarks under comparable conditions and even surpassing many H 2 O 2 -mediated systems. This study offers a facile method to synthesize high-spin surface Fe IV = O and highlights the importance of metal spin state tailoring on non-enzymatic methane activation. High-spin Fe(IV) = O sites efficiently activate methane but are challenging to synthesize. This study develops dual Fe(II) sites on FeS 2 , generating high-spin Fe(IV) = O from O 2 , achieving superior methane-to-methanol conversion under mild conditions.